Respuesta :

When you multiply a number with an exponent by a number with an exponent, you add the exponents together.

For example:

[tex]x^{2} *x^{3} =x^{2+3}=x^5[/tex]

[tex]y^{1} (y^3)=y^{1+3}=y^4[/tex]

[tex]2^2*2^3=2^{2+3}=2^5[/tex]


When an exponent is negative, you move it to the other side of the fraction to make the exponent positive

For example:

[tex]x^{-2}[/tex]  or  [tex]\frac{x^{-2}}{1}=\frac{1}{x^2}[/tex]

[tex]\frac{1}{y^{-3}}=\frac{y^3}{1}[/tex]  or  y³



So:

[tex]4^3*4^{-5}=4^{3+(-5)}=4^{-2}[/tex]

[tex]4^{-2}=\frac{1}{4^2}=\frac{1}{16}=0.0625[/tex]


a.) correct

b.) correct

c.) incorrect

d.) correct

e.) correct

f.) incorrect

g.) incorrect